RI 3335 Cooperative Fuel Research Motor-Gasoline Survey, Summer 1936 ? Introduction (321d4804-a8c9-4bf2-a5ee-1d11ccaffd99) (The National Institute for Occupational Safety and Health (NIOSH), 1937)
This is the second of a series of reports on properties of commercial motor fuels made pursuant to a cooperative agreement between the Cooperative Fuel Research (C.F.R.) Committee and the Bureau of Mines of the Department of the Interior. The first report gave data on motor gasolines sold during the winter of 1935-36.3/ These gasoline surveys report results of inspections, in oil-company laboratories, of samples of gasoline obtained by representatives of oil companies from service-station pumps in marketing areas throughout the country. In the present survey are presented inspection data on 239 samples of regular-price gasoline, 166 samples of premium-price gasoline, and 157 samples of third-grade gasoline, a total of 562 samples collected during the summer of 1936.